Comparative effectiveness of loop diuretics on mortality in the treatment of patients with chronic heart failure: a multicenter propensity score matched analysis - Täger, Tobias; Fröhlich, Hanna; Seiz, Mirjam; Schellberg, Dieter; Katus, Hugo; Frankenstein, Lutz (International journal of cardiology, 2019)
Background - Loop diuretics are given to the majority of patients with chronic heart failure (HF). Whether the different pharmacological properties of the three guideline-recommended loop diuretics result in differential effects on survival is unknown. - Methods - 6293 patients with chronic HF using either bumetanide, furosemide or torasemide were identified in three European HF registries. Patients were individually matched on both the respective propensity scores for receipt of the individual drug and dose-equivalents thereof. - Results - During a follow-up of 35,038 patient-years, 652 (53.7%), 2179 (51.9%), and 268 (30.4%) patients died amongst those prescribed bumetanide, furosemide, and torasemide, respectively. In univariable analyses of the general sample, bumetanide and furosemide were both associated with higher mortality as compared with torasemide treatment (HR 1.50, 95% CI 1.31-1.73, p<0.001, and HR 1.34, CI 1.18-1.52, p<0.001, respectively). Mortality was higher in bumetanide users when compared to furosemide users (HR 1.11, 95% CI 1.02-1.20, p=0.01). However, there was no significant association between loop diuretic choice and all-cause mortality in any of the matched samples (bumetanide vs. furosemide, HR 1.03, 95% CI 0.93-1.14, p=0.53; bumetanide vs. torasemide, HR 0.98, 95% CI 0.78-1.24, p=0.89; furosemide vs. torasemide, HR 1.02, 95% CI 0.84-1.24, p=0.82). The results were confirmed in subgroup analyses with respect to age, sex, left ventricular ejection fraction, NYHA functional class, cause of HF, rhythm, and systolic blood pressure. - Conclusions - In patients with HF, mortality is not affected by the choice of individual loop diuretics.
Gesehen am 11.09.2019